THE ROLE OF RK-3 IEM IN THE FARGONA VALLEY POWER GRID AND FEATURES AND ADVANTAGES OF THE INTEGRATED GAS TURBINE - B. B. Abdurahimov (Journals Park Publishing, 2024)
In this article, the problems of the electrical system of industrial enterprises, several mode parameters in addition to the scheme parameters given in the determination of the electrical network mode, including the active power in the electrical system, the active and reactive loads of consumers, and the distribution parameters between the node voltage for all variable modes complex optimization and evaluation criteria of active-reactive power from mode parameters were studied and researched.
Keywords: Active and reactive power, transformers, design process, complex optimization, natural method, Synchronous compensator, Synchronous drives.